2018
DOI: 10.21037/tgh.2018.04.05
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment and tumor cells: two targets for new molecular therapies of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC), is one of the most frequent human cancer and is characterized by a high mortality rate. The aggressiveness appears strictly related to the liver pathological background on which cancer develops. Inflammation and the consequent fibro/cirrhosis, derived from chronic injuries of several origins (viral, toxic and metabolic) and observable in almost all oncological patients, represents the most powerful risk factor for HCC and, at the same time, an important obstacle to the efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 130 publications
(136 reference statements)
1
34
0
Order By: Relevance
“…Although the role of the tumor microenvironment in tumor progression is well established (Amicone and Marchetti, ; Kamil and Rowe, ), the cross‐talk between HSC and HCC cells in liver cancer metastasis has hardly been explored. Our previous study showed that activated HSCs create an immunosuppressive microenvironment in an orthotopic liver tumor mouse model by inducing expansion of the Tregs and MDSCs (Zhao et al , ) (Zhao et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of the tumor microenvironment in tumor progression is well established (Amicone and Marchetti, ; Kamil and Rowe, ), the cross‐talk between HSC and HCC cells in liver cancer metastasis has hardly been explored. Our previous study showed that activated HSCs create an immunosuppressive microenvironment in an orthotopic liver tumor mouse model by inducing expansion of the Tregs and MDSCs (Zhao et al , ) (Zhao et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Several types of cells in the tumor microenvironment (immune cells, endothelial cells, and fibroblasts, etc.) support this process [74,75]. Fibrosis is particularly important for HCC development as 80-90% of the cases develops in a background of advanced liver fibrosis and cirrhosis [5].…”
Section: Activated Hscs/cafs Hcc Drug Resistance and Hcc Immunotherapymentioning
confidence: 96%
“…Thus, the increase of both Raf and PCNA in the lung parenchyma surrounding NDMA-induced lung tumors suggesting an important lung tumor–macrophage interaction ( Ramakrishna et al, 2002 ). IL-1β is also able to contribute to fibrosis while TNF-α increases anti-apoptotic signals to avoid cell death ( Amicone & Marchetti, 2018 ). Importantly, while carcinogens can induce inflammation, chronic inflammation can also increase carcinogen exposure and uptake within the body by weakening barrier functions ( Greten & Grivennikov, 2019 ).…”
Section: Mechanisms Of Pro-tumorigenic Activity By Carcinogensmentioning
confidence: 99%